The Effect of Return On Equity and Current Ratio on Firm Value with Capital Structure as an Intervening Variable in Food And Beverage Sub-Sector Companies Listed on the Indonesia Stock Exchange for the Period 2017-2021 - Anggita Rani Fauziah; Bertilia Lina Kusrina; Gatot Subiyakto; Ira Phajar Lestari (Journal of Economic, Bussines and Accounting (COSTING), 2024)
A growing number of people are showing an interest in investing for the long haul by putting their money into the capital markets. The food and beverage industry is one of these that industry 4.0 has identified as a priority. With more and more companies joining the Indonesia Stock Exchange, it's getting harder for companies to stand out and attract investors by raising their company value. For the years 2017–2021, this research set out to examine the relationship between firm value, return on equity, current ratio, and capital structure among food and beverage companies traded on the Indonesia Stock Exchange. This study's sample was determined using a purposive sampling strategy utilising data from 10 different companies. The secondary data used in this study was sourced from the Indonesia Stock Exchange's website (www.idx.co.id) as well as from connected companies' official websites. The data is analysed using SPSS 25 software and a multiple linear regression analysis model, as well as path analysis. The findings indicate that Capital Structure is significantly impacted to a lesser extent by Return On Equity and Current Ratio. Firm Value is somewhat affected by Return On Equity, although it is unaffected by Current Ratio and Capital Structure. Return On Equity (ROE) has no mediating influence on business value via capital structure. In contrast, capital structure acts as an intervening variable in the current ratio, which has an indirect impact on firm value